TGF-beta signal transduction: biology, function and therapy for diseases - Yan Tie; Fan Tang; Dandan Peng; Ye Zhang; Huashan Shi (Molecular Biomedicine, 2022)
Abstract The transforming growth factor beta (TGF-β) is a crucial cytokine that get increasing concern in recent years to treat human diseases. This signal controls multiple cellular responses during embryonic development and tissue homeostasis through canonical and/or noncanonical signaling pathways. Dysregulated TGF-β signal plays an essential role in contributing to fibrosis via promoting the extracellular matrix deposition, and tumor progression via inducing the epithelial-to-mesenchymal transition, immunosuppression, and neovascularization at the advanced stage of cancer. Besides, the dysregulation of TGF-beta signal also involves in other human diseases including anemia, inflammatory disease, wound healing and cardiovascular disease et al. Therefore, this signal is proposed to be a promising therapeutic target in these diseases. Recently, multiple strategies targeting TGF-β signals including neutralizing antibodies, ligand traps, small-molecule receptor kinase inhibitors targeting ligand–receptor signaling pathways, antisense oligonucleotides to disrupt the production of TGF-β at the transcriptional level, and vaccine are under evaluation of safety and efficacy for the forementioned diseases in clinical trials. Here, in this review, we firstly summarized the biology and function of TGF-β in physiological and pathological conditions, elaborated TGF-β associated signal transduction. And then, we analyzed the current advances in preclinical studies and clinical strategies targeting TGF-β signal transduction to treat diseases.